2020
DOI: 10.1111/bju.15031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different minimally invasive percutaneous nephrostomy sheaths for the treatment of staghorn stones

Abstract: are first co-authors and contributed equally to this work. ObjectiveTo compare the safety and effectiveness of using a conventional nephrostomy sheath (NS) vs using a new NS with suction and evacuation functions in minimally invasive percutaneous nephrolithotomy (MPCNL) for the treatment of staghorn stones. Patients and MethodsA prospective and randomised study of 60 patients with staghorn stones randomly assigned into two groups of 30 patients. One group underwent MPCNL using conventional NS, whereas the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Three studies containing operative time data [ 15 , 16 ] were analyzed, and the results indicated that the operative time of the vacuum-assisted sheath group was significantly reduced compared to that of the conventional sheath group (MD = − 15.74; 95% CI − 1944, − 12.04, P < 0.00001), with insignificant heterogeneity (I 2 = 0%, P = 0.91) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies containing operative time data [ 15 , 16 ] were analyzed, and the results indicated that the operative time of the vacuum-assisted sheath group was significantly reduced compared to that of the conventional sheath group (MD = − 15.74; 95% CI − 1944, − 12.04, P < 0.00001), with insignificant heterogeneity (I 2 = 0%, P = 0.91) (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al reported a higher incidence of postoperative fever [ 15 ]. Due to the small size of the sheath, high-pressure perfusion is very often performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Xu et al prospectively randomized 66 patients with staghorn stones to suctioning MPCNL using the ClearPetra sheath and nonsuctioning traditional MPCNL. They reported 86.7% SFR in the suctioning group compared with 70% in the traditional MPCNL [17] (Table 1).…”
Section: Percutaneous Nephrolithotomymentioning
confidence: 99%
“…However, the high stone-free rate (SFR) of PNL often needs to establish multiple access tracts, and the increased number of tracts is the risk factor for postoperative complications, especially bleeding [ 3 , 4 ]. Minimally invasive PNL (mPNL) use the size of 16F to 20F tract sheath [ 5 ], which has advantages of lower postoperative bleeding rate and similar SFR [ 6 , 7 ], but a disadvantage of lower intraoperative therapeutic efficiency [ 8 ]. With the rapid development of endoscopic equipment, flexible ureteroscope (FURS) has been accepted by most urologists to treat renal stones < 2 cm [ 2 , 9 ], Even for some stones ≥ 2 cm [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%